Analýza a návrh řešení slevového serveru - Bruštík, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Tato bakalářská práce se zabývá analýzou fungujícího elektronického obchodu společnosti Liquid Design s.r.o.. Provádí nezbytný výzkum jeho současné situace z ekonomického hlediska, a také z pohledu informatiky. Pomocí zjištěných údajů poté představuje adekvátní postup ke zlepšení a tedy naplnění cílů.

This bachelor thesis is dealing with an analysis of a functional electronic shop owned by company Liquid Design s.r.o.. It performs necessary research of current situation from economic point of view and also from informatics perspective. Based on the collected data it then introduces an adequate process to improve and thus to fullfill the objectives.
Analysis and Design of Coupon & Discount E-commerce Model
Keywords: Elektronický obchod; e-shop; e-business; e-commerce; analýza; marketing; SEO; slevový server; Electronic commerce; e-shop; e-business; e-commerce; analysis; marketing; SEO; discount server